Features of role positions of subjects of social and pedagogical advocacy - Ekaterina Valentinovna Alekhina (Вестник Майкопского государственного технологического университета, 2023)
The article considers social and pedagogical advocacy on the rights of minors. This technology is a relevant tool for the protection of rights and legitimate interests of minors today. The author characterizes the features of the role positions of subjects of social and pedagogical advocacy. The study was conducted on the basis of the results of social protection activities of VROOI “A Glimmer of Hope” (Voronezh) public organization. Social and pedagogical advocacy is a type of activity in which parents of children whose rights and legitimate interests are violated, public organizations or active citizens organize activities to protect a specific violated right or legitimate interest of a minor that affects his successful socialization and upbringing. The subjects whose role positions are characterized include minors, whose rights and legitimate interests require social and pedagogical advocacy, their parents and representatives of public organizations that implement social and pedagogical advocacy in practice. Each of the subjects is considered according to the degree of its participation in advocacy, personal characteristics that allow implementing social and pedagogical advocacy with varying degrees of success. Role positions are considered on the example of children with disabilities and their parents. The author describes difficulties in the process of interaction between the subjects of advocacy, which may have a negative impact on the effectiveness of advocacy.